Assessing threats to shallow groundwater quality from soil pollutants in Glasgow, UK: development of a new screening tool. (19th November 2018) - Fordyce, F. M.; Ó Dochartaigh, B. É.; Bonsor, H. C.; Ander, E. L.; Graham, M. T.; McCuaig, R.; Lovatt, M.
ABSTRACT: A new GIS-based screening tool to assess threats to shallow groundwater quality has been trialled in Glasgow, UK. The GRoundwater And Soil Pollutants (GRASP) tool is based on a British Standard method for assessing the threat from potential leaching of metal pollutants in unsaturated soil/superficial materials to shallow groundwater, using data on soil and Quaternary deposit properties, climate and depth to groundwater. GRASP breaks new ground by also incorporating a new Glasgow-wide soil chemistry dataset. GRASP considers eight metals, including chromium, lead and nickel at 1622 soil sample locations. The final output is a map to aid urban management, which highlights areas where shallow groundwater quality may be at risk from current and future surface pollutants. The tool indicated that 13% of soil sample sites in Glasgow present a very high potential threat to groundwater quality, due largely to shallow groundwater depths and high soil metal concentrations. Initial attempts to validate GRASP revealed partial spatial coincidence between the GRASP threat ranks (low, moderate, high and very high) and groundwater chemistry, with statistical correlation between areas of high soil and groundwater metal concentrations for both Cr and Cu ( r 2 >0.152; P <0.05). Validation was hampered by a lack of, and inconsistency in, existing groundwater chemistry data. To address this, standardised subsurface data collection networks have been trialled recently in Glasgow. It is recommended that, once available, new groundwater depth and chemistry information from these networks is used to validate the GRASP model further.